Tracheal breach revealed by post-operative facial edema: a case report - Driouich, Aicha; Ouachaou, Jamal; Sidayne, Mohammed; El Khattab, Fatimazahra; Zarrouki, Youssef (Frontiers in Anesthesiology, 2026)
Post-intubation tracheal breach is rare but constitutes a serious postoperative complication following general anesthesia. Clinical manifestations are often non-specific, ranging from simple facial edema to acute respiratory distress, sometimes mimicking emergencies such as anaphylaxis. We report the case of a 43-year-old female, ASA I, scheduled for laparoscopic cholecystectomy, who developed progressive facial and cervico-thoracic edema three hours after extubation, initially suggesting an allergic reaction. Subsequent investigations including chest CT and bronchoscopy confirmed a tracheal rupture. The patient was successfully managed conservatively. This case emphasizes the importance of early differential diagnosis when confronted with unusual postoperative edema.